2020
DOI: 10.1101/2020.09.08.288738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

L-ascorbic acid (vitamin C) fermentation by the human pathogenVibrio cholerae

Abstract: L-ascorbic acid, commonly known as vitamin C, is a ubiquitous 6-carbon carbohydrate characterized by its ability to scavenge free radicals. In enteric bacteria, L-ascorbate can be utilized as a nutrient using the UlaABCDEF and UlaG-UlaRpathway under anaerobic conditions. In this study, we identified homologs of the Ula system within Vibrio cholerae and showed that V. cholerae is able to utilize L-ascorbate as an energy source. Growth pattern assays of a ulaG in-frame deletion mutant demonstrated that ulaG is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recently, V. cholerae has been shown to utilize L-ascorbate as an energy source. Interestingly, Boyd and colleagues grew V. cholerae in M9CAS medium containing glucose or L-AA [ 30 ]. On the other hand, we carried out our growth experiments in LB medium.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, V. cholerae has been shown to utilize L-ascorbate as an energy source. Interestingly, Boyd and colleagues grew V. cholerae in M9CAS medium containing glucose or L-AA [ 30 ]. On the other hand, we carried out our growth experiments in LB medium.…”
Section: Resultsmentioning
confidence: 99%
“…V. cholerae is demonstrated to alternatively use L-ascorbate (Vitamin C), a micronutrient, as an energy source, and it has to compete with the commensal microbiota for it. To determine the role of L-ascorbate in V. cholerae , Rosenberger et al, showed that V. cholerae with defective L-ascorbate utilization machinery is unable to compete in vitro when grown in an M9 minimal media with supplementation of casamino acids and intestinal mucus, and they conclude that the fermentation of the metabolite may be significant in an in vivo phenotype [85] . Some commensal anaerobes can produce several essential vitamins for the human body, including vitamin K and the water-soluble vitamin B12 [86] .…”
Section: Microbiota-specific Colonization Resistance Mechanismsmentioning
confidence: 99%
“…Recently, Vibrio cholerae is shown to utilize L-ascorbate as energy source. Interestingly, Boyd and colleagues grew Vibrio cholerae in M9CAS medium containing glucose or L-AA [20]. On the other hand, we carried out our growth experiments in LB medium.…”
Section: Viability Of Vibrio Cholerae Strains Is Severely Compromised...mentioning
confidence: 99%